A Critical Analysis of the Challenges in Teaching Kitab Kuning from a Pesantren Pedagogical Perspective - Naufal Hamzah Putra; Rofi'ah, Siti (Journal Of Islamic Education And Pesantren, 2023)
This study aims to critically analyze the problems of kitab kuning learning from the perspective of pesantren pedagogy by highlighting linguistic, motivational, methodological, and learning-environment dimensions. The study of kitab kuning as the primary academic tradition in Islamic boarding schools holds a strategic position in the transmission of turats (classical Islamic scholarship) and the formation of students’ Islamic intellectual reasoning. However, in practice, the learning process faces various challenges, particularly in mastering instrumental sciences (nahwu–sharaf), low learning motivation among some students, limited methodological variation that remains predominantly teacher centered, and environmental factors that influence concentration and instructional effectiveness. This research employs a qualitative approach with a case study design in the pesantren context, utilizing observation, in-depth interviews, and documentation, analyzed through a descriptive-critical framework. The findings reveal that linguistic barriers constitute the dominant factor affecting text comprehension, while traditional instructional models such as bandongan and sorogan have not been fully complemented by reflective and participatory pedagogical approaches. Students’ motivation is influenced by their perception of the relevance of kitab kuning to contemporary needs, while the pesantren learning environment plays an ambivalent role as a space for character formation and, at the same time, a challenge in academic management. Critically, this study affirms that kitab kuning learning retains strong epistemological and cultural value, yet requires pedagogical revitalization through the integration of contextual approaches, strengthening of textual literacy, and diversification of instructional strategies.